Sarana Penelusuran Informasi di UPT Perpustakaan Proklamator Bung Hatta Bukittinggi - Reynaldi, Reynaldi; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This paper discusses about informational browsing media in UPT Perpustakaan Proklamator Bung Hatta Bukittinggi the purpose of this paper are: to describe; (1) how is informational browsing device. is in UPT. Perpustakaan Proklamator Bung Hatta Bukittinggi; (2) is there is any problem that UPT. Perpustakaan Proklamator Bung Hatta Bukittinggi face in providing informational browsing media; (3) is there is any effort that UPT. perpustakaan Proklamator Bung Hatta Bukittinggi do in facing any problem in providing informational browsing media in UPT. perpustakaan Proklamator Bung Hatta Bukitinggi. The writing methods of this paper are descriptive methods, data gathered by observatioan way, interviewing and library studying. Based on data analysis, it can be concluded: first, UPT. perpustakaan Proklamator Bung Hatta Bukittinggi use OPAC (Online Public Acces Catalogue) as a browsing device, as acatalogue, bibliography, index and abstract that have been changed into digital or electronical form. Ofserasises UPT. perpustakaan Proklamator Bung Hatta Bukittinggi media by using ILMS program ( Integrated Library Management system) eithers in circulation service, guess book and OPAC informational browsing media. Second, problem found are; (1) unconrected web to internet and electrical down; (2) lack of human resource with library background; (3) lack of use knowledge with the using of browsing device,third, efforts to do: (1) increase the wifi speed and use generator set machine to anticipate electrical down; (2) add some librarians into the member of library who have library background and; (3) do some library guideness to the member of library so librarians could use browsingmedia that avaible in that library.Keywords: information retrieval; OPAC